Landscape, culture, and belonging : writing the history of Northeast India - Neeladri Bhattacharya,Ed; Joy L.K Pachuau (CUP, 2019)
This collection of essays is an important contribution to the new literature on frontier studies and the historiography of Northeast India. Moving away from an exclusive dependence on colonial ethnographies, the authors build their arguments on a varied range of sources: from buranjis to revenue records, survey maps to explorers' diaries, and missionary papers to police files. They question the givennes of the categories through which the region is usually described, and contest the stereotypes by which the people of the region are primitivized. They explore the historical processes whereby the region was surveyed, mapped, understood, represented, politically governed, economically refigured, and historically constituted during the colonial period. Though focused on the experience of Northeast India, the volume also raises substantive questions about the idea of the frontier and the border, the primitive and the modern, and the tribal and the settled, the local and the trans-local.